Applying augmented reality in a university English class: Learners' perceptions of creativity and learning motivation. Issue 2 (15th March 2023) - Lin, Yu-Ju; Wang, Hung-chun
ABSTRACT: This study was conducted to explore the effects of an augmented-reality (AR) creative project on English L2 learners' perceptions of creativity, as well as to investigate how to stimulate students' learning motivation. The AR project was developed and integrated into the course syllabus of a university English class, and 39 Taiwanese freshmen completed the project step by step. Data for analysis primarily emerged from the Preference Scale, the Instructional Materials Motivation Survey (IMMS), and an AR student survey. Following a pretest-posttest design, this study showed that the participants demonstrated a higher level of favorable perceptions of creative thinking, such as preference for ideation and valuing new ideas, and a lower tendency for premature critical evaluation of ideas, although these differences were non-significant. However, working on the project also led to a significantly higher level of self-awareness of being too busy for new ideas. According to the results of the IMMS, attention yields significantly positive relationships with relevance, confidence, and satisfaction . This finding suggests that the students who were more engaged tended to see the project as relevant to their needs; they were also more confident and had a more satisfying AR experience. Based on the results, pedagogical implications are discussed.